A Switchable Ultra-Wideband Metamaterial Absorber with Polarization-Insensitivity and Wide-incident Angle at THz Band - Wang, Liansheng; Xia, Dongyan; Fu, Quanhong; Ding, Xueyong; Wang, Yuan (Frontiers in Materials, 2021)
In this paper, we report a switchable ultra-wideband metamaterial absorber with polarization-insensitivity and wide-incident angle at THz band which is composed of VO2 disk, polyimide dielectric substrate, and gold ground plane. The results show that the absorption is greater than 90% from 3.5THz to 8THz for a temperature of 300K and this absorption band disappears when the temperature rises to 350K. The absorption property of our proposed metamaterial absorber is insensitive to polarization states and angles and it can withhold high absorption of more than 80% for wide-incident angles, up to 60°for TE mode and TM mode. The wideband absorption mechanism is elucidated using an effective medium and surface current analysis.